Prevalence of depression and factors associated with it in geriatric population in rural area of Vadodara, Gujarat - Jadav, Pranay; Patel, Maharshi V. (International Journal Of Community Medicine And Public Health, 2017)
Background: Geriatric depression is becoming a global public health problem causing considerable morbidity and disability. This problem is also increasing in India but still not sufficient work has been done on depression in many parts of India. This study aimed to find out prevalence of and factors associated with depression in elderly population in Vadodara, Gujarat. Methods: A community based cross sectional study was performed among 176 participants of more than 60 years of age. Simple random sampling was done to select talukas, villages and participants. Depression was screened by Geriatric Depression Scale-15 (GDS 15). Person with score more than 5 was considered as depressed. Descriptive and bivariate analysis was conducted with the help of SPSS version 11.5 for windows. Results: The overall prevalence of depression in old age was 34.1% but in female it was higher (64.7%) than male (14.81%). Bivariate analysis revealed that gender (OR=10.64, 95% CI: 5.093 – 21.82), p<0.001), lower education (OR=4.167, 95% CI: 1.991 – 8.719, p<0.001) and cognitive impairment (MMSE score) (OR=121.333, 95% CI: 37.384 – 393.79, p<0.001) were independently associated with depression. Conclusions: Gender, lower education and cognitive impairment are some of the factors associated with depression in older population.